A self-amplifying RNA vaccine provides protection in a murine model of bubonic plague - Shattock, Robin John; Andrianaivoarimanana, Voahangy; McKay, Paul F.; Randriantseheno, Lovasoa Nomena; Murugaiah, Valarmathy; Samnuan, K.; Rogers, Paul; Tregoning, John S.; Rajerison, Minoarisoa; Moore, Kristoffer M.; Laws, Thomas Robert; Williamson, E. Diane (Frontiers in Microbiology, 2023)
Mice were immunised with a combination of self-amplifying (sa) RNA constructs for the F1 and V antigens of Yersinia pestis, at dose-levels of 1µg or 5µg or with the respective protein sub-units as a reference vaccine. Immunisation of outbred OF1 mice on day 0,28 with the lowest dose used (1µg) of each of the saRNA constructs in lipid nanoparticles, protected 5/7 mice against subsequent sub-cutaneous challenge on day 56 with 180 cfu (2.8 MLD) of a 2021 clinical isolate of Y. pestis termed 10-21/S, and 5/7 mice were protected against 1800 cfu (28MLD) of the same bacteria. By comparison, only 1/8 or 1/7 negative control mice immunised with 10µg of irrelevant haemagglutin RNA in lipid nanoparticles (LNP), survived challenge with 2.8MLD or 28MLD Y. pestis 10-21/S, respectively. BALB/c mice were also immunised with the same saRNA constructs and responded with the secretion of specific IgG to F1 and V, neutralising antibody for the V antigen and developed a recall response to both F1 and V. These data represent the first report of an RNA vaccine approach using self-amplifying technology and encoding both of the essential virulence antigens, providing efficacy against Y. pestis. This saRNA vaccine for plague has potential for further development, particularly since its amplifying nature has the potential to induce immunity with less boosting. It is also amenable to rapid manufacture with simpler downstream processing than for protein sub-units, enabling a rapid deployment and surge manufacture during disease outbreaks.